THE RIGHT TO SEXUAL AND REPRODUCTIVE HEALTH OF LGBTIQ PERSONS AND THE CHALLENGES OF BIOMEDICAL ASSISTED REPRODUCTION - Simić, Jelena (Pravni zapisi, 2022)
The mass application of modern medical biotechnology (BAF) andits expansion on a global level have brought numerous challenges at theindividual and social level, and the very goal of reproductive technologieshas exceeded the treatment of infertility. For LGBTIQ people, the use ofBAF in the first place is a matter of reproductive justice that should provideeveryone, without distinction, economic, social and political powerand resources to make healthy decisions about their bodies, sexuality andreproduction for themselves, their families and their union. The reality,however, is that access to BAF is enjoyed by a small privileged group ofpeople, and many medically infertile persons do not seek BAF because ofthe high cost of such treatment. As a result, the development of biomedicaltechnology is increasingly becoming a subject of reconsideration andcontroversy, and less and less an achievement that supports life and health.In this paper, the author discusses when and why access to BAF becamea matter of the LGBTIQ rights and whether access to BAF can really beequal for all, given its costs? Finally, the author refers to BAF in terms ofdomestic legislation and concludes the paper with a call for changes to thelegal solution that prohibits the use of BAF for LGBTIQ individuals andcouples in Serbia.
Keywords: biomedically assisted fertilization (BAF); family; parenthood; modern society; LGBTIQ persons; sexual and reproductive health and rights